Pengaruh Perilaku Pengelolaan Keuangan terhadap Penerima Kartu Indonesia Pintar pada Mahasiswa UPN â€Veteranâ€ Jawa Timur - Dinda Mariana; Eko Purwanto; Ira Wikartika (Universitas Batanghari Jambi, 2022)
Students as the young generation must understand managing finances wisely as a prosperous financial growth and development in the present and in the future. Financial management behavior as a measure of student success in dealing with their finances. This study aims to determine the effect of financial knowledge, financial attitude, and locus of control on financial management behavior. The population for this study were students who received the Indonesian Smart College Card (KIP-K) UPN